2004
DOI: 10.1016/j.febslet.2004.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of SARS‐CoV main protease and identification of biologically active small molecule inhibitors using a continuous fluorescence‐based assay

Abstract: Severe acute respiratory syndrome associated coronavirus main protease (SARS-CoV Mpro) has been proposed as a prime target for anti-SARS drug development. We have cloned and overexpressed the SARS-CoV Mpro in Escherichia coli, and purified the recombinant Mpro to homogeneity. The kinetic parameters of the recombinant SARS-CoV Mpro were characterized by high performance liquid chromatography-based assay and continuous fluorescence-based assay. Two novel small molecule inhibitors of the SARS-CoV Mpro were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 24 publications
3
48
0
Order By: Relevance
“…Novel antiviral targets for SARS coronavirus and influenza A virus have been identified previously using small compoundbased forward chemical genetics approaches similar to ours. 25,38,39 In this study, we identified ten compounds among approved drugs with as primary hits in chemical library screening that possess antiviral activities. Some may offer potential therapies in the evolving MERS-CoV epidemic.…”
Section: Discussionmentioning
confidence: 99%
“…Novel antiviral targets for SARS coronavirus and influenza A virus have been identified previously using small compoundbased forward chemical genetics approaches similar to ours. 25,38,39 In this study, we identified ten compounds among approved drugs with as primary hits in chemical library screening that possess antiviral activities. Some may offer potential therapies in the evolving MERS-CoV epidemic.…”
Section: Discussionmentioning
confidence: 99%
“…(11)) showed an activity of 2.5 M in enzyme-based and 7 M in Vero cell-based assays while binding to the target enzyme in a non-covalent way. Similar analogues could be identified from a 50,000-member compound library by a continuous fluorescence-based assay [127].…”
Section: The Sars-coronavirus Main Proteinasementioning
confidence: 99%
“…A number of small molecules that interfere with the viral replication process were identified and subsequently examined more closely using a Vero cell-based plaque reduction assay, a pseudotype viral S protein/ACE2-mediated entry assay, and in vitro analysis of inhibition of the 3CL protease and helicase enzymes [1159]. MP576 (416) [1160], HE602 (417) and VE607 (418) inhibited 3CL protease, helicase and viral entry, respectively, with micromolar IC 50 s and were active at similar concentrations in the plaque reduction assay. A more definitive confirmation of the viral targets in the cell-based assays awaits selection of resistant virus and the mapping of mutations.…”
Section: Sars Cov Inhibitors -Generalmentioning
confidence: 99%